Criteria for First-Year Growth Response to Growth Hormone Treatment in Prepubertal Children With Growth Hormone Deficiency: Do They Predict Poor Adult Height Outcome? - Straetemans, Saartje; De Schepper, Jean; Thomas, Muriel; Tenoutasse, Sylvie; Beauloye, Véronique; Rooman, Raoul (Frontiers in Endocrinology, 2019)
Objective: Several criteria for first-year growth response (FYGR) to growth hormone (GH) treatment have been proposed. We explored which FYGR criteria predicted best the final height outcome after GH treatment in prepubertal children with GH deficiency (GHD). Design and methods: Height data of 129 GHD children (83 boys) who attained adult height and had been treated with GH for at least 4 consecutive years with at least one year before pubertal onset, were retrieved from the Belgian GH Registry. The FYGR parameters were: (1) increase in height (∆Ht) SDS, (2) height velocity (HV) SDS, (3) ∆HV (cm/year), (4) index of responsiveness (IoR) in KIGS prediction models, (5) first-year HV SDS based on the KIGS expected HV curve (HV KIGS SDS), (6) near final adult height (nFAH) prediction after first-year GH treatment. Poor final height outcome (PFHO) criteria were: (1) total ∆Ht SDS <1.0, (2) nFAH SDS <-2.0, (3) nFAH minus midparental height SDS <-1.3. ROC curve analyses were performed to define the optimal cut-off for FYGR parameters. Only ROC curves with an area under the curve (AUC) >70% were further analyzed. Results: Twelve, 22 and 10% of the children had respectively a total ∆Ht SDS <1, nFAH SDS <-2, and nFAH minus midparental height SDS <-1.3. The AUC’s ranged between 73 and 85%. The highest AUC was found for first-year ∆Ht SDS to predict total ∆Ht SDS <1, and predicted nFAH SDS to predict nFAH SDS <-2. The currently used FYGR criteria had low specificities and sensitivities to detect PFHO. To obtain a 95% specificity, the cut-off value (and sensitivity) of FYGR parameters were: ∆Ht SDS <0.35 (40%), HV SDS <-0.85 (43%), ∆HV <1.3 cm/year (36%), IoR <-1.57 (17%), HV KIGS SDS <-0.83 (40%) to predict total ∆Ht SDS <1; predicted nFAH SDS (with GH peak) <-1.94 (25%), predicted nFAH SDS (without GH peak) <-2.02 (25%) to predict nFAH SDS <-2. At these cut-offs, the amount of correctly diagnosed poor final responders equals the amount of false positives. Conclusion: First-year growth response criteria perform poorly as predictors of poor final height outcome after long-term GH treatment in prepubertal GHD children.